Audit of Antenatal Steroid Use in Mothers of Preterms Admitted to a Neonatal Intensive Care Unit in Ghana - Sackey, A.H.; Tagoe, L.G. (Ghana medical journal, 2018)
Background Antenatal corticosteroids (ACS) are established as an effective method of reducing preterm morbidity and mortality. At the Korle Bu Teaching Hospital (KBTH), a tertiary referral centre in Ghana, it is recommended that a course of ACS should be given to mothers before delivery between 24 weeks to 34 weeks gestation. Objectives The study was performed primarily to determine the level of adherence to guidelines on administration of ACS. Methods All babies with gestational ages up to 34 weeks admitted to the neonatal unit (NICU) during the period of the study were eligible for inclusion. Results There were 214 eligible admissions during the study period, of which 93 babies (43%) were studied due to poor access to medical records. Dexamethasone was the only steroid used, and mothers of 65 (70%) of the 93 babies received at least one dose; 17 (18%) received only one dose, 35 (38%) - 2 doses, 9 (10%) - 3 doses, and 4 (4%) - 4 doses. Conclusions This study has shown a low uptake of antenatal corticosteroids, similar to other low-income and middle-income countries. To improve preterm survival and morbidity, there is an urgent need to increase the use of corticosteroids before preterm deliveries in Ghana and other low-income and middle-income countries.
Keywords: Antenatal corticosteroids; Prematurity; Neonatal intensive care; Audit; Low-income countries